Revision of the subgenus Persexarthrus Voss of the genus Anthonomus Germar (Coleoptera: Curculionidae: Anthonomini) - Košťál, Michael (Zootaxa, 2014)
The subgenus Persexarthrus Voss, 1944 of the weevil genus Anthonomus Germar, 1817 is revised. Anthonomus (Persexarthrus) behnei sp. n. is described. A neotype of Bradybatus ornatoides Reitter, 1898 and lectotypes for Anthonomus baudueri var. abeillei Desbrochers des Loges, 1892, A. cyprius Marshall, 1925 and Neobradybatus variabilis Hoffmann, 1963 are designated. The five species of the subgenus are described, keyed and their distributions given.